Analisis Yuridis Penguasaan Tanah Masyarakat Hukum Adat - Ardinal, Benni; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The iregulation ion ithe isystem iof iland itenure ipracticed iby iindigenous ipeople iin ithe iRegulation iof iLegislation ishowed ithat ithe irecognition iof ithe iexistence iof iindigenous ipeople iwith iregard ito ithe iaspect iof iland, iforestry, iplantation, iand iliving ienvironment ihas ibeen ivery istrong iand iit ihas ibeen iproven ithat isuch iarrangement ihas ibeen istated iin ithe iRegulation iof iLegislation, ialthough, iup ito inow, ithere iis ino iharmonious ilegal iinstrument iandadequate iimplementation iyet. iThe iposition iof ilaw (legal iposition) iover ithe isystem iof iland itenure ipracticed iby iindigenous ipeople iis ifactually istill irecognized iby ithe icommunity. Where ithe iadat iland exists iis icurrently istill irecognized, ibut ijuridically, ithe iexistense iof ithe iadat iland ihas inot ibeen iable ito ibe iimplemented ibecause iLocal iRegulation ifor ithat ipurpose ihas inot ibeen iissuedyet. iAccording ito ithe iDecision iof iConstitutional iCourt ion iadat iforest. iAdat iForest iis ithe iforest ibelongs iof ithe ilocal iindigenous ipeople iand iit ican ibe iused ias ia iguideline iin ithe iissuance iof ilocal iRegulation. iThe ilegal iaction itaken iwas iby iadvocating ithe icommunity ito isocialize ithe iDecision iof iConstitutional iCourt iNo i35/ iPUU-X/ i2012 iand iprovide irecommendations ito ithe igovernment ito iissue ia iLocal iRegulation.